Gradual and Acute Temperature Rise Induces Crossing Endocrine, Metabolic, and Immunological Pathways in Maraena Whitefish (Coregonus maraena) - Rebl, Alexander; Verleih, Marieke; Nipkow, Mareen; Altmann, Simone; Bochert, Ralf; Goldammer, Tom (Frontiers in Genetics, 2018)
The complex and still poorly understood nature of thermoregulation in various fish species complicates the determination of the physiological status on the basis of diagnostic marker genes and indicative molecular pathways. The present study aimed to compare the physiological impacts of both gradual and acute temperature rise from 18 °C to 24 °C on maraena whitefish in aquaculture. Microarray-based transcriptome profiles in the liver, spleen and kidney of heat-stressed maraena whitefish revealed the modulation of a significantly higher number of genes in those groups exposed to gradually rising temperatures compared with the acutely stressed groups, which might reflect early adaptation mechanisms. Moreover, we suggest a common set of 11 differentially expressed genes that indicate thermal stress induced by gradual or acute temperature rise in the three selected tissues. Besides the two pathways regulated in both data sets unfolded protein response and aldosterone signaling in epithelial cells, we identified unique tissue- and stress type-specific pathways reflecting the crossroads between signal transduction, metabolic and immunologic pathways to cope with thermal stress. In addition, comparing lists of differentially regulated genes with meta-analyzed published data sets revealed that “acute temperature rise”-responding genes that encode members of the HSP70, HSP90 and HSP40 families; their functional homologs; co-chaperones and stress-signal transducers are well conserved across different species, tissues and/or cell types and experimental approaches.